Flow based immuno/bioassay and trends in micro-immuno/biosensors - Supaporn Kradtap Hartwell (2018)
The term immuno/bioassay refers to analytical techniques that utilize the specific molecular recognition between antibodies and antigens or between biomolecules and specific receptors. Features such as high selectivity and low sample consumption make them very useful for analysis of samples with complex matrices. However, immuno/bioassays involve time-consuming (multi-step) operations which usually consist of steps of multiple incubation and washing. These are tedious and may result in large errors. Automatted immuno/bioassay systems can ease and shorten these processes and thus are highly beneficial. The hyphenation of flow-based techniques (i. e. flow injection related techniques and micro-fluidic systems) with immuno/bioassay protocols paves a new way for performing such assays. Compared to conventional micro-plate formats, flow-based immuno/bioassays can reduce the time needed for analysis, the volumes of samples and reagents consumed, and the need for trained personnel. In order to transform immuno/bioassays from conventional to flow-based formats, the solid surfaces used for the immobilization step has to be changed in order to meet the specific requirements of flow systems. To further develop the on-site analytical systems in micro-fluidic platforms, improvements in detection methods are necessary for high-sensitivity and rapid measurement. This review overviews the advantages and disadvantages of flow-based immuno/bioassay formats, the various types of solid surfaces for immobilization, and the methods of detection. Trends to improve sensitivity, speed and robustness are emphasized. © Springer-Verlag 2010.